PENGARUH PERSONAL BRANDING TASYI ATHASYIA TERHADAP KEPUTUSAN MENJADI SUBSCRIBERS CHANNEL YOUTUBE TASYI ATHASYIA (Survei Pada Followers Akun Instagram @tasyiiathasyia) - Marissa Dhyantirahma, (2020)
YouTube is a video sharing platform that is currently the most popular in the world. Tasyi Athasyia is one of Indonesian Youtubers who joined into the food and cooking category. The number of subscribers in a YouTube channel determines how successful the channel is. The purpose of this research is to examine the influence of Tasyi Athasyia's personal branding on the decision to become subscribers on Tasyi Athasyia's YouTube channel. The approach used is a quantitative approach. The theory used in this research is Theory of Reasoned Action. The survey was conducted on 100 followers of Instagram account @tasyiiathasyia. Based on the test results of the coefficient of determination, Tasyi Athasyia's personal branding affected the decision to become Tasyi Athasyia's YouTube channel subscribers by 62.2%, and the remaining 37.8% was determined by other factors not examined. Based on the calculation results of the significance test, it can be concluded that t arithmetic> t table (5.105> 1.9844), which means that Ho is rejected and Ha is accepted. This means that there is an influence between Tasyi Athasyia's personal branding on the decision to become subscribers on Tasyi Athasyia's YouTube channel.